Kompaktno mesto in njegova družbena percepcija - Rogatka, Krzysztof (Urbani izziv, 2015)
This article examines the Polish city of Torun in terms of the compact city concept. It analyses the theoretical elements of the compact city concept using Torun as a case study and taking into account the psychological aspects (i.e., social perception) of a compact city. The case study collected primary data during fieldwork in 2013 and 2014. The methodology consists of a literature review, satellite photo grid analysis (250 * 250 m) and social perception of the compact city (n = 128) assessed through questionnaires with representative quantitative data. The research was also supplemented with an analysis of the accessibility of the main sites in Torun. The results are presented on a map of urban areas and graphs of social perception. The study concludes that Torun is a compact city from the urban point of view, but it is not perceived as such from the psychological or social points of view.
Keywords: mesta; Poland; Poljska; rast; trajnostnostni razvoj; urbanism; urbanistični razvoj; urbanizem